Analysis of Basic Physics Laboratory Competency Attainment Among Biology Students Based on Laboratory Assessment Results - Laode Manarfah; Ahmad Dahlan; Dirgah Kaso Sanusi; Ahmad Yani; Trisno Setiawan (Journal of Physics Education : Review and Research, 2026)
This study aimed to analyze the attainment of Basic Physics laboratory competencies among Biology students based on laboratory assessment results. A descriptive quantitative approach was employed using secondary data obtained from laboratory assessment records. The data included students’ scores for each laboratory unit, total scores, average scores, final laboratory grades, and laboratory completion status. Data were analyzed using descriptive statistical techniques, including mean, standard deviation, percentage, and competency achievement categories. The results showed that students generally demonstrated good laboratory performance. A total of 73.69% of the students were classified in the High and Very High competency categories, indicating satisfactory competency attainment. The analysis of laboratory units revealed that all experimental units achieved either High or Very High categories. Unit 5 obtained the highest average achievement (93.61%), while Unit 3 recorded the lowest average score (79.73%). The findings also indicated that students who did not complete the minimum required laboratory units tended to obtain lower final grades. The study concludes that the Basic Physics laboratory program contributed positively to the development of students’ practical competencies. Laboratory assessment data can be utilized as an important source of information for evaluating competency attainment and improving laboratory learning practices.